Integrasi Risiko Geologi Dalam Instrumen Tata Ruang: Analisis Isi Regulasi RTRW Kabupaten Pohuwato 2025-2045 - Dicky Rahmansyah S. Tone; Wahyulin Ws. Harunja; Siti Qamariyah Bunga; Aprilia Mohune; Sri Maryati; Ronal Hutagalung (-, 2026)
Fifteen relevant articles/paragraphs were identified and evaluated across three analytical dimensions: the existence of geological hazards within spatial patterns, the depth of zoning control instruments, and potential spatial conflicts between settlement allocations and hazard-prone zones. The strongest control instruments are the seismic KRB provisions incorporating PGA and MMI parameters (Article 96(10)) and the mandatory tsunami risk assessment requirement (Article 96(16)). Five structural weaknesses were identified: absence of coordinate-based non-buildable zones, lack of Gorontalo Fault data integration, absence of liquefaction hazard provisions, no climate change projections, and lack of an operational RDTR. Significant spatial conflicts were identified in coastal urban settlements overlapping with high-level tsunami and flash flood hazard zones. Detailed geological mapping at 1:25,000 scale, geohazard-based RDTR, and mandatory site-specific hazard assessment procedures are required prior to building permit issuance in high KRB zones.